1979
DOI: 10.1002/1097-0142(197909)44:3<1066::aid-cncr2820440340>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral tumor and diffuse central nervous system infiltration complicating acute myelogenous leukemia

Abstract: An intracerebral space occupying lesion was found in a 20-year-old woman with acute myelogenous leukemia (AML) when she was in complete hematological remission. Computerized tomography of the brain demonstrated the tumor in the roof of the third ventricle and its subsequent resolution after cranial irradiation and intraventricular cytosine-arabinoside. This form of central nervous system complication in AML has not been previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Leukemic intracranial space occupying lesions are rare, and in the literature, there are only 13 reported cases of intracranial leukemic mass lesions in the course of the disease [3][4][5][6][7]. Our patient developed left hemiparesis and leukemic mass was found and removed from the right temporal lobe.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Leukemic intracranial space occupying lesions are rare, and in the literature, there are only 13 reported cases of intracranial leukemic mass lesions in the course of the disease [3][4][5][6][7]. Our patient developed left hemiparesis and leukemic mass was found and removed from the right temporal lobe.…”
Section: Introductionmentioning
confidence: 80%
“…On CT study, only 4-7.5% of leukemic patients were diagnosed as having intracranial mass in the course of their disease [12,13]. A search of the literature revealed only 13 reported cases of intracranial leukemic mass (9 cases of ALL, 4 cases of AML) were diagnosed in the course of their disease [3][4][5][6][7]. Of these cases, 9 cases had supratentorial and 4 cases had infratentorial lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colors other than green are due to different concentrations of the enzyme within the cells or different states of oxidation of the enzyme. 22 Thus, granulocytic sarcoma or myeloblastoma are preferable terms. 1,3,23,24 Central nervous system (CNS) involvement is a well-recognized complication of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…In 1981, Petursson and Boggs [22] reviewed 67 previously published cases of spinal cord involvement in leukemia patients and found that 31 had acute myeloid leukemia. Clinical features and therapeutic modalities in welldocumented recent reports of CNS granulocytic sarcoma are summarized in Table 2 [2,6,7,20,[22][23][24][25][26][27][28][29][30][31][32]. Most of the previously published cases of CNS granulocytic sarcoma developed in older patients; the clinical and biological significance of this complication of leukemia in pediatric patients is obscure.…”
Section: Discussionmentioning
confidence: 99%